The AC conductivity of samarium phosphate glasses - Budi, Agus Setyo; Ayof, Mohd Nizam; Ahmad, Asmala; Lau, K.T. (Universiti Teknikal Malaysia Melaka, 2006)
The AC conductivity of SIGMA(AC) samarium phosphate glasses with different Sm2O3 content is measured in frequency range of 10^3 to 10^7 hz over the temperature range of300 to 553 K. The observed frequency dependence can be expressed as SIGMA(AC)=AW^s, where 0.6 < s < 1 which confirms the electron hopping phenomena. The bulk conductivity increases with the increasing temperature and decreases with the increasing neodymium content.